The Correlation between Parity and Residence with Maternal Mortality Due to Miscarriage and Abortion in Papua Province in 2020 - Laily, Dian; Prasetyo, Budi; Dwi Jayanti, Ratna (Jurnal Ilmiah Kesehatan, 2025)
The Maternal Mortality Ratio (MMR) in Papua Province was 289 per 100,000 live births in 2017, rising to 565 per 100,000 live births by 2020. This study analyzes the correlation between parity and residence with maternal mortality due to miscarriage and abortion in Papua Province. This paper was a retrospective cross-sectional study. The population was comprised of reproductive-aged women aged 15-49 who participated in the Indonesia Demographic and Health Survey (IDHS) 2020. There were 14,802 respondents by total sampling. Bivariate analysis used logistic regression at a 95% confidence level (α=0.05). The results showed that most respondents had less than or equal to three-born children (83.64%) and lived in rural areas (72.06%). In addition, 14.35% of them died due to miscarriage and abortion. The logistic regression test results on the parity variable indicated p=0.000 and negative Odds Ratio (OR)=0.475. It indicated respondents with more than three-born children had a higher risk of maternal mortality compared to those with less than or equal to three-born children. In addition, the test results of the residency variable showed p=0.000 and negative OR=0.394. It implied that respondents who lived in urban areas faced a higher risk of maternal mortality due to miscarriage and abortion compared to rural mothers. In conclusion, parity and residence significantly correlate with maternal mortality due to miscarriage and abortion.